Efficacy of various plant-derived interventions in the prevention of radiation dermatitis in breast cancer patients: a systematic review and network meta-analysis of randomised controlled trials - Li, Mingyu; Hao, Jianping; Song, Guoming; Zhang, Ming; Zhang, Bo; Hao, Yunran; Zhao, Lijun (Frontiers in Oncology, 2025)
ObjectiveRadiation dermatitis (RD), a common adverse event among breast cancer patients undergoing post-surgical radiotherapy, may be mitigated through the application of plant-derived substances possessing radioprotective effects. However, comprehensive evaluations comparing the efficacy of different plant-derived compounds are not yet available. The objective of this study is to perform a network meta-analysis (NMA) to evaluate the efficacy of diverse plant-derived substances in preventing RD in patients with breast cancer.MethodsA systematic search was conducted to identify randomized controlled trials (RCTs) published up to April 2025 that investigated the use of plant-derived substances for the prevention of RD in patients with breast cancer. Two authors individually screened the articles, gathered pertinent information, and conducted quality assessments of the studies that were included.Data were synthesized and analyzed using Stata version 15.1.ResultsIn our NMA, we included 18 RCTs involving 2177 patients and 18 different treatment arms. Regarding the primary and secondary outcomes, Sylimarin derived from Silybum marianum L.(Milk thistle) (SUCRA = 0.934) and Cichorium intybus L.(Chicory) root extract (SUCRA = 0.72) demonstrated the greatest efficacy in mitigating the occurrence of grade ≥2 and grade ≥3 RD. Furthermore, Silymarin (RR = 0.05, 95% CI [0.00, 0.87]) exhibits greater efficacy compared with the standard of care (SOC) in preventing grade ≥2 RD. However, no intervention demonstrated superiority over SOC in preventing grade ≥3 RD.ConclusionSilymarin has shown promise as treatment for the prevention of grade ≥2 RD in patients undergoing radiotherapy. Future studies with larger sample sizes are needed to substantiate the efficacy of various plant-derived substances.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251063723.